The land reclamation along the Hai-Ho river and the birth of modern Tianjin (1897-1937) - Ma, Rui (International Planning History Society Proceedings, 2018)
Within the early decades of the twentieth century, the city of Tianjin transformed from a traditional trade terminal to a modern city. The size of settlement expanded more than 10 times during these years which made Tianjin the second largest city in China at that time. For the special natural environment, the topography cannot be neglected in this process. By analyzing of the aquatic environment and topographic condition along the Hai-Ho River, comparing Chinese traditional attitude to water and modern concept of hygiene, and reviewing urban development of concessions before 20th century, this paper argue that land reclamation was a vital and necessary work in building a modern city. Using archive of land filling of Hai-Ho Conservancy Commission, the paper explores the process of land reclamation along the Hai-Ho River and examines the important role of the commission, new filling method and technology in this process. It then focuses on the development of the concessions on the west bank of the river and examines how the land filling evolved in the complex relationship and played an important role.